Functional Outcomes of Varus Osteotomy with Locking Compression Plate Fixation in Legg-Calve-Perthes Disease - Leeprakobboon, Duangjai; Sukpanichyingyong, Sermsak; Sangkomkamhang, Thananit (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: Patients with Legg-Calve-Perthes disease are treated to preserve the roundness of the femoral head. Surgical treatment includes the proximal femur or acetabulum operations, however, remains controversial. Herein, we investigated the clinical findings and outcomes of varus osteotomy with locking compression plate fixation. Methods: We reviewed 19 children (20 hips) with Legg-Calve-Perthes disease who underwent varus osteotomy with locking compression plate fixation at our hospital. The time to re-ossification, Stulberg classification, and Harris hip score were recorded preoperatively and at the final follow-up. Results: We included 16 boys and two girls with unilateral hip involvement and one girl with bilateral hip disease. The mean age at the time of surgery was 7.9 years. Based on the Catterall classification, one, 10, and nine patients were classified as grades II, III, and IV, respectively. All patients were followed for 33 months. The mean time to re-ossification was 167 days. At final follow-up, based on the Stulberg classification, seven, nine, and four patients were categorized as class II, III, and IV, respectively. Based on the Harris hip score, 21.1%, 47.7%, and 31.6% of patients showed excellent, good, and fair functional outcomes, respectively. The Harris hip scores at the final follow-up were significantly improved compared to preoperative values. Following adjustment for sex and disease severity, age at disease onset and time of surgery were associated with Harris hip scores. Conclusions: Varus osteotomy with locking compression plate fixation yields good results and significantly improves functional outcomes, although patient age affects the outcomes.